2012
DOI: 10.5402/2012/786549
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Draining Patterns of Right Pulmonary Veins at the Hilum and an Anatomical Classification

Abstract: Pulmonary veins carry oxygenated blood from the lungs to the left atrium. Variations are quite common in the pattern of drainage. The present study was undertaken to evaluate the incidence of different draining patterns of the right pulmonary veins at the hilum by dissecting the human fixed cadaveric lungs. Clinically, pulmonary veins have been demonstrated to often play an important role in generating atrial fibrillation. Hence, it is important to look into the anatomy of the veins during MR imaging and CT an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…However, in the present study, pulmonary artery variations were observed in 78.57% of right hilum and only 8.11% of left hilum. In the present case, pulmonary vein variation was observed in 47.62% of right lungs and 42.24 % of left lungs which is comparable with the finding of 46.03% of variations in pulmonary venous anatomy of dissected lungs observed in a study [23]. The pulmonary veins are the dominant source of ectopic depolarization initiating atrial fibrillation in the majority of patients with paroxysmal atrial fibrillation [24].…”
Section: Discussionsupporting
confidence: 89%
“…However, in the present study, pulmonary artery variations were observed in 78.57% of right hilum and only 8.11% of left hilum. In the present case, pulmonary vein variation was observed in 47.62% of right lungs and 42.24 % of left lungs which is comparable with the finding of 46.03% of variations in pulmonary venous anatomy of dissected lungs observed in a study [23]. The pulmonary veins are the dominant source of ectopic depolarization initiating atrial fibrillation in the majority of patients with paroxysmal atrial fibrillation [24].…”
Section: Discussionsupporting
confidence: 89%